Antioxidant capacity of Maillard reaction products' fractions with different molecular weight distribution from chicken bone hydrolysate – galactose system. (8th May 2017) - Nie, Xiaohua; Zhao, Liming; Regenstein, Joe M.; Xu, Dan; Meng, Xianghe
Summary: Maillard reaction products (MRP) were prepared from an aqueous chicken bone hydrolysate (CBPH) – galactose systems by heating at 100 °C for up to 7.5 h without pH control, and then separated into the <3‐, 3‐ to 10‐ and >10‐kDa fractions using ultrafiltration. Antioxidant capacity and spectral properties of these MRP fractions were studied. The scavenging activity towards DPPH and hydroxyl radicals as well as reducing power of each MRP fraction increased with the heating time, in accordance with the increase in UV absorbance, browning and fluorescence intensity. For the same MRP, the fraction with high molecular weight (MW) demonstrated the stronger radical scavenging activity and reducing power than that with low MW. Radical scavenging activities of MRP fractions largely depended on their MW, while their reducing powers were more related to the reaction progress. These results suggested that antioxidant capacity of MRP fractions should be positively related to its molecular size. Abstract : Maillard reaction products (MRP) fractions from chicken bone protein hydrolysate – galactose system had antioxidant capacity, and the high‐molecular weight (MW) one is the main antioxidant compounds. Antioxidant action of MRP fraction was positively correlated with its spectral properties.